The War as a Media Spectacle. The Central American Press in the Great War (1917) - Vega Jiménez, Patricia (Historia y Comunicación Social, 2013)
United States participation in the Great War of 1917 was the outcome of multiple factors, one of them was the pressure excerted by the main news papers around the world. Central American press, particulary from Costa Rica and El Salvador was not the exception; influenced the United States´ government into deciding to participate in the conflict suffered by Europe by applying multiple strategies. This study analyzes these strategies and the roll played by the Central American press during the process.